What factors determine brand communication? A hybrid brand communication model from utilitarian and hedonic perspectives - Fang, Lingzhi Brian; Liu, Mingzhen; Tang, Liu (Frontiers in Psychology, 2023)
Introduction With the advancement of new media, brand communication has been taken into consideration by lots of firms. Apparently, customer affection plays a significant role in brand communications, though few studies have determined how the twofold of information function works in this communication mechanism. Based on this research gap and practical background, this paper proposes a hybrid model of communication comprising the utilitarian and hedonic aspects. Methods For this study, 575 questionnaires were collected, followed by the structural equation modeling of the derived data to test the research model. Results The results of statistical analysis show that the brand communication can be improved in terms of both utilitarian and hedonic aspects. Moreover, psychological contract and customer engagement play a chain mediation role in this mechanism. Discussion These findings contribute to the research of brand communication mechanism in digital era. Likewise, the findings offers several practical implications to the brand management.